2003
DOI: 10.1089/107555303322524535
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-Endocrine-Immune Response to Mindfulness-Based Stress Reduction in Individuals Infected with the Human Immunodeficiency Virus: A Quasiexperimental Study

Abstract: These results provide tentative evidence that MBSR may assist in improving immunity in individuals infected with HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(105 citation statements)
references
References 46 publications
6
91
0
8
Order By: Relevance
“…other MBSR studies (39,80). Attendance rates dropped during the first 4 sessions and then stabilized, consistent with other MBSR studies in which dropouts occurred early (81).…”
Section: Sephton Et Alsupporting
confidence: 87%
See 1 more Smart Citation
“…other MBSR studies (39,80). Attendance rates dropped during the first 4 sessions and then stabilized, consistent with other MBSR studies in which dropouts occurred early (81).…”
Section: Sephton Et Alsupporting
confidence: 87%
“…Analyses controlling for the effects of pain and sleep difficulties in the relationship between MBSR and depres- 80 …”
Section: Resultsmentioning
confidence: 99%
“…We also conducted a study in HIV+ men to evaluate the immune effects of MBSR. We found that MBSR normalized aspects of immune function that were dysregulated in these men (Robinson, et al, 2003). Others have also reported evidence of immune benefits of MBSR.…”
Section: Introductionsupporting
confidence: 67%
“…In patients with breast cancer, MBSR increases activity in peripheral mononuclear cells, suggesting potential beneficial effects of MBSR on cell longevity in this setting. 8 In addition, use of MBSR has been associated with increased natural killer cell activity in patients with human immunodeficiency virus (although no significant clinical differences), 9 lower inflammatory responses, 9 increase in antibody titers to an influenza vaccine 10 and improvements in immune system function after strenuous physical stress.…”
Section: Physiologymentioning
confidence: 99%